Research on AI natural language understanding and generation algorithm based on deep learning - Fan, Guoqing (Proceedings of SPIE, the international society for optical engineering, 2024)
In order to explore the application of deep learning technology in natural language processing, this article provides a detailed analysis of various algorithms, including language models, syntactic analysis, semantic understanding, and text generation. The results indicate that by adopting advanced neural network models and rich datasets, the accuracy and efficiency of language processing can be significantly improved, thereby promoting the performance and adaptability of intelligent systems in practical applications.